1973
DOI: 10.1007/bf01868223
|View full text |Cite
|
Sign up to set email alerts
|

On the recovery of adhesiveness by trypsin-dissociated cells

Abstract: Summary.A sensitive method for assaying aggregation of dissociated cells has been developed which allows the determination of the mean number of cells per aggregate of a cell population. We have demonstrated that exposure of dissociated 6-or 7-day chick embryo neural retinal cells to trypsin in calcium-free solution renders them unable to aggregate for a half hour in stirred cell suspensions. Aggregation was noticeable first at 30 to 40 minutes and progressed to the formation of massive compact aggregates. Bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

1974
1974
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(29 citation statements)
references
References 107 publications
2
27
0
Order By: Relevance
“…The correlation between the characteristic temperature for cell adhesion and membrane fluidity was not observed in the presence of Mg 2 § Since the two divalent cations, Ca 2+ and Mg 2 § are considered to act in qualitatively different ways in cell adhesion (27,29), it is probable that Mg 2+ is effective in cell adhesion in such a manner that is independent of the change in membrane fluidity at about 10~ SUMMARY BHK 21 cells can adhere to a protein-coated plastic dish in the presence of Ca 2+ at temperatures above 12~ However, they cannot adhere below 8~ The ESR spectrum of cells spin-labeled with a stearic acid label indicated that the membrane fluidity changed characteristically at 10~ 20~ and 300C. The critical temperature for cell adhesion coincided well with one of the characteristic temperatures for the membrane fluidity change.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The correlation between the characteristic temperature for cell adhesion and membrane fluidity was not observed in the presence of Mg 2 § Since the two divalent cations, Ca 2+ and Mg 2 § are considered to act in qualitatively different ways in cell adhesion (27,29), it is probable that Mg 2+ is effective in cell adhesion in such a manner that is independent of the change in membrane fluidity at about 10~ SUMMARY BHK 21 cells can adhere to a protein-coated plastic dish in the presence of Ca 2+ at temperatures above 12~ However, they cannot adhere below 8~ The ESR spectrum of cells spin-labeled with a stearic acid label indicated that the membrane fluidity changed characteristically at 10~ 20~ and 300C. The critical temperature for cell adhesion coincided well with one of the characteristic temperatures for the membrane fluidity change.…”
Section: Discussionmentioning
confidence: 96%
“…The change in the physical state of the lipids may also affect the insertion (13) and distribution (3,4,8,20,23) of proteins in the membrane, and the activity of membrane-bound enzymes (31). These molecular events would also be relevant to cell adhesion (12,24,27,30).…”
Section: Discussionmentioning
confidence: 99%
“…C ELL-CELL interactions are fundamental to all aspects of animal development, as well as to the functioning of the mature organism. Since the pioneering experiments of Steinberg et al (1973) and Takeichi (1977), it has become clear that a major role in these interactions is played by calcium-dependent adhesion systems. Calcium-dependent adhesion is accomplished principally through the actions of the cadherins, a family of cell surface glycoproteins (reviewed by Takeichi, 1988).…”
mentioning
confidence: 99%
“…2c). Trypsin destroys the cell-to-cell adhesion molecules such as adhesion receptor, and enables cells a singlecell suspension state which makes it an effective reagent to detach adherent cells (Edwards et al 1975;Steinberg et al 1973). Recombinant trypsin is more suitable for the production of pharmaceutical proteins because it is non-toxic and free of virus contamination.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in the cell culture process trypsin is often used to detach cells, which can destroy the cellto-cell adhesion molecules (Edwards et al 1975;Steinberg et al 1973), thereby enabling cells to stay in single-cell suspension state. Nowadays, there are still some commercial trypsins derived from animal pancreas, which may be toxic and cause infectious contamination to cultured cells (Golden et al 2002).…”
Section: Introductionmentioning
confidence: 99%